2013
DOI: 10.1051/0004-6361/201220768
|View full text |Cite
|
Sign up to set email alerts
|

Towards understanding the relation between the gas and the attenuation in galaxies at kpc scales

Abstract: Context. Understanding the relation between the attenuation and the gas is fundamental for interpreting the appearance of galaxies. This can now be done down to a local scale in the local Universe, thanks to the high spatial resolution achievable from the farultraviolet (FUV) to the far-infrared (FIR). More importantly, this relation is also crucial for predicting the emission of galaxies. This is essential in semi-analytic models that link dark matter from large cosmological simulations, to the baryonic matte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 144 publications
3
36
0
Order By: Relevance
“…The gas metallicity is a direct indicator of dust attenuation and dust content within molecular clouds. Again, whenever the attenuation is high, which is generally the case when the molecular phase is dominant (Boquien et al 2013), the interstellar radiation field cannot penetrate and dissociate the molecular gas phase and thus reduce the M(H 2 )/M(Hi) ratio.…”
Section: Molecular-to-atomic Gas Scaling Relationsmentioning
confidence: 99%
“…The gas metallicity is a direct indicator of dust attenuation and dust content within molecular clouds. Again, whenever the attenuation is high, which is generally the case when the molecular phase is dominant (Boquien et al 2013), the interstellar radiation field cannot penetrate and dissociate the molecular gas phase and thus reduce the M(H 2 )/M(Hi) ratio.…”
Section: Molecular-to-atomic Gas Scaling Relationsmentioning
confidence: 99%
“…This code has been successfully used to reconstruct the star formation history of high-z and local galaxies Boquien et al 2016;Lo Faro et al, in prep. ), including those of the HRS (Boquien et al 2012(Boquien et al , 2013Ciesla et al 2014Ciesla et al , 2016.…”
Section: Modelsmentioning
confidence: 99%
“…The FUV heated dust emission can also be tracked using the total infrared (TIR) emission (see Hao et al 2011;Galametz et al 2013;and Boquien et al 2013). We tried three different ways of computing the TIR emission and concluded that 24 μm traces the TIR within 0.09 dex.…”
Section: Sfr and Sfe Hmentioning
confidence: 99%